Book reviews - Herbert, Daniel and Stanek, Tom and Peterson, Elizabeth and Deutsch, James and Coyne, Michael and Schnherr, Johannes and Lund, Andrew and Kramer, Gary M and Scatton-Tessier, Michelle (Film International, 2005)
Ernesto R. Acevedo-Muoz Buuel and Mexico: The Crisis of National Cinema Berkeley: University of California Press, 2003 Kelly Asbury Dummy Days: America's Favourite Ventriloquists from Radio and Early TV Santa Monica: Angel City Press, 2003 Rikke Schubert and Anne Gjelsvik, eds. Femme Fatalities: Representations of Strong Women in the Media Sweden: Nordicom, 2004 Ryan Gilbey Groundhog Day (BFI Modern Classics) London: British Film Institute, 2004 Paul Buhle and Dave Wagner Hide in Plain Sight: Hollywood Blacklistees in Film and Television, 1950-2002 New York: Palgrave Macmillan, 2005 C. McGivern and Fred Landesman Ronald Reagan: The Hollywood Years Bracknell: Sammon Publishing, 2005 Tom Mes Iron Man: The Cinema of Tsukamoto Godalming: FAB Press, 2005 Lew Hunter Lew Hunter's Screenwriting 434: The Industry's Premier Teacher Reveals the Secrets of the Successful Screenplay New York: Perigee Books, 2004 Christine Geraghty My Beautiful Laundrette . The British Film Guide 9 (Turner Classic Movies British Film Guides) London: I.B. Tauris, 2005 Susan Hayward Simone Signoret: The Star as Cultural Sign London: Continuum, 2004
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9maWluLjMuNS40Ng